2012
DOI: 10.4172/2157-7560.1000130
|View full text |Cite
|
Sign up to set email alerts
|

Designing Vaccines against Human Papillomavirus and Hepatitis B Virus: Similarities and Differences for Preventable Viral Infections and role of AS04 Adjuvant System in Addressing Specific Challenges

Abstract: IntroductionSeveral intracellular pathogens can establish long-lasting chronic infections and may lead to clinical disease. Two examples of such pathogens are the Human papillomavirus (HPV) and the Hepatitis B virus (HBV). Immunological mechanisms are involved both in the establishment and maintenance of the tolerance to these infections. Chronic infections and diseases are the results of a delicate interplay between the pathogen's actions to survive in the host and the attempts of the immune system to eradica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 153 publications
(191 reference statements)
0
1
0
Order By: Relevance
“…Nonetheless, it would be interesting to investigate in future studies whether the proportion of particulates in the nanometer range correlates with a greater or lesser immunogenicity. As a TLR4 agonist, MPL is capable of directly activating key innate immune mechanisms, including the activation of APCs and the induction of proinflammatory cytokines, such as IFN-γ, TNF-α, IL-6, and IL-12, which in turn enhance the adaptive immune response, that is, induce Th cells and B cell responses. Because of the addition of MPL, AS04 is more effective in enhancing the immunogenicity of antigens as compared with insoluble aluminum salts only. , This additive effect was also observed with other adjuvants. For example, Beck (2018) reported that combining the saponin liposome adjuvant with an insoluble aluminum salt resulted in an adjuvant with more potent adjuvant activity .…”
Section: Results and Discussionmentioning
confidence: 99%
“…Nonetheless, it would be interesting to investigate in future studies whether the proportion of particulates in the nanometer range correlates with a greater or lesser immunogenicity. As a TLR4 agonist, MPL is capable of directly activating key innate immune mechanisms, including the activation of APCs and the induction of proinflammatory cytokines, such as IFN-γ, TNF-α, IL-6, and IL-12, which in turn enhance the adaptive immune response, that is, induce Th cells and B cell responses. Because of the addition of MPL, AS04 is more effective in enhancing the immunogenicity of antigens as compared with insoluble aluminum salts only. , This additive effect was also observed with other adjuvants. For example, Beck (2018) reported that combining the saponin liposome adjuvant with an insoluble aluminum salt resulted in an adjuvant with more potent adjuvant activity .…”
Section: Results and Discussionmentioning
confidence: 99%